![image](https://tex.z-dn.net/?f=tg3x%3Dt+%5C%5C+3%5E%7B1%2B2t%7D-10%2A3%5Et%2B3%3D0+%5C%5C+3%2A3%5E%7B2t%7D-10%2A3%5Et%2B3%3D0+%5C%5C++%5C%5C+3%5Et%3Dy+%5C%5C+3y-10y%2B3%3D0+%5C%5C+D%3D100-4%2A3%2A3%3D64%3D8%5E2+%5C%5C+y_1%3D3%3By_2%3D1%2F3++%5C%5C+%5C%5C+3%5Et%3D3%3D%3Et_1%3D1+%5C%5C+3%5Et%3D1%2F3%3D%3E3%5Et%3D3%5E%7B-1%7D%3D%3Et_2%3D-1+%5C%5C++%5C%5C+tg3x%3D1%3D%3E3x%3D+%5Cpi%2F4%2B+%5Cpi+n%2C+n%5Cin+Z%3D%3Ex_1%3D+%5Cpi+%2F12%2B+%5Cpi+n%2F3%2Cn%5Cin+Z+%5C%5C+tg3x%3D-1%3D%3E3x%3D+-%5Cpi%2F4%2B+%5Cpi+k%2C+k%5Cin+Z%3D%3Ex_2%3D+-%5Cpi+%2F12%2B+%5Cpi+k%2F3%2Ck%5Cin+Z)
t_1=1 \\ 3^t=1/3=>3^t=3^{-1}=>t_2=-1 \\ \\ tg3x=1=>3x= \pi/4+ \pi n, n\in Z=>x_1= \pi /12+ \pi n/3,n\in Z \\ tg3x=-1=>3x= -\pi/4+ \pi k, k\in Z=>x_2= -\pi /12+ \pi k/3,k\in Z" alt="tg3x=t \\ 3^{1+2t}-10*3^t+3=0 \\ 3*3^{2t}-10*3^t+3=0 \\ \\ 3^t=y \\ 3y-10y+3=0 \\ D=100-4*3*3=64=8^2 \\ y_1=3;y_2=1/3 \\ \\ 3^t=3=>t_1=1 \\ 3^t=1/3=>3^t=3^{-1}=>t_2=-1 \\ \\ tg3x=1=>3x= \pi/4+ \pi n, n\in Z=>x_1= \pi /12+ \pi n/3,n\in Z \\ tg3x=-1=>3x= -\pi/4+ \pi k, k\in Z=>x_2= -\pi /12+ \pi k/3,k\in Z" align="absmiddle" class="latex-formula">